Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Satellite-anchored UAV sensing system for high-resolution soil moisture mapping - Muhammad Ibrahim Rana; Hamza Rafique; Hassan Jaleel (Computers and Electronics in Agriculture, 2026)

A Column Perfusion Study to Test Semi-Interpenetrating Polymer Embedded Biochar Based Slow-Release Fertilizers Efficiency in Mitigating Nutrients Leaching - Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. F. Al-Farraj; Munir Ahmad; Taieb Aouak; Hamed Ahmed Al-Swadi (Water, Air, & Soil Pollution, 2026)

Rationalizing bud load for grapevine cv sugraone for balanced yield and superior fruit quality in a warm semi-arid region - Muhammad Hashir Khan; Irfan Ali; Muhammad Tahir Akram; Mahmood-ul-Hassan; Adeel Anwar; Rizwan Rafique (Acta Physiologiae Plantarum, 2026)

Molecular target for neuroinflammation and pain management: transient receptor potential vanilloid 1 - Zunera Chauhdary; Muhammad Saad Masood; Muhammad Irfan; Amina Shafi; Duryab Rafique; Abeesha Arif; Maryam Akmal (Inflammopharmacology, 2026)

Protective effects of zinc and Prunus amygdalus against cadmium-induced nephrotoxicity in male Albino rats - Muhammad Talha Ishaq; Faiza Zubair; Naila Riaz; Hira Kanwal; Ayesha Tehreem Shahbaz; Tooba Tahir; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Journal of Trace Elements in Medicine and Biology, 2026)

Deoxynivalenol-induced hepatic and renal injury via pyroptosis under heat stress conditions - Jingdi Zhang; Amna Rafique; Jie Liu; Muhammad Saqlain; Bo Yang; Ding Zhang; Ruiyan Niu; Zilong Sun (Toxicology Letters, 2026)

Integrated approach for arsenic prediction and health risk evaluation in community tube wells installed by public health department: comparative study of random forest, extreme gradient boosting, and deep neural networks - Ibad Ullah; Sebnem Arslan; Zahid Ullah; Zhanlong Chen; María V. Esteller; Hafiz Ullah; Muhammad Afaq Hussain; Waqar Ali; Rafique Ahmad (Environmental Geochemistry and Health, 2026)

Integrated ADME, metabolomics, and multi-target docking of Novel methoxy- and thiophene-substituted benzodioxane hydrazones - Aisha Rafique; Kanwal Rehman; Shagufta Kamal; Muhammad Sajid Hamid Akash (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

Three-dimensional modelling of key parameters impacting the steam electrolysis in solid oxide electrolysis cell for clean hydrogen production - Azeem Mustafa; Yong Shuai; Zhijiang Wang; Alfredo Iranzo; Guene Lougou Bachirou; Muhammad Rafique; Muhammad Ammad Nasir; Samia Razzaq (Fuel, 2026)

Anti-arthritic effect of Helicteres isora L. ethanolic extract via modulation of cytokines and oxidative stress in CFA-induced arthritic rats - Muhammad Muzammil Nazir; Azhar Rafique; Salma Sultana; Asma Ashraf (Inflammopharmacology, 2026)

Comparative study of holo-cellulose nanofibers for citral-encapsulated Pickering emulsions: Structure-property relationships and antibacterial performance - Yayue Wang; Qiaoyangzi Lei; Shuai Zhang; Muhammad Kashif Iqbal Khan; Hamad Rafique; Tian Ren (Food Chemistry, 2026)

Recent advances in biochar-based materials for CO₂ capture: From preparation to application in value-added chemicals and fuels - Maroof Ali Panhwar; Boxi Geng; Bachirou Guene Lougou; Muhammad Rafique; Imran Ali; Rehan Khursheed; Akhil Garg; Yong Shuai (Journal of Environmental Chemical Engineering, 2025)

Highly adhesive, stretch, antioxidative and antibacterial double-network hydrogel containing artemisinin for infected wound closure and healing - Xinxiang Chai; Ruifei Ge; Yanzhen Lou; Fozil Mamaraim Ugli Turaqulov; Khaydar E. Yunusov; Lei Nie; Muhammad Rafique Khan; Guohua Jiang (Chemical Engineering Journal, 2025)

Cystic fibrosis in Pakistan: population harbouring rare variants non-responsive to CFTR modulators and the dilemma of poor health facilities - Anum Safdar; Muhammad Usman Ghani; Iqbal Bano; Tahir Mehmood; Hassan Rafique; Muhammad Farooq Sabar; Ali Akbar; Rehan Sadiq Shaikh (Molecular Biology Reports, 2025)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Economic growth and sustainable material innovation in the circular economy: Dynamic ARDL evidence on environmental and technological moderators - Dhekra Ben Amara; Rim Ben Arfi; Muhammad Rafique; Achraf Ghorbal; Yong Shuai (Journal of Environmental Management, 2025)

Synergistic co-catalyst strategies for photo-thermal CO2 reduction into value-added fuels: A critical review on mechanisms, challenges, and future prospects - Maroof Ali Panhwar; Bachirou Guene Lougou; Muhammad Rafique; Wei Wang; Mustafa Azeem; Boxi Geng; Hao Zhang; Achraf Ghorbal; Yong Shuai (Fuel, 2025)

Monte-Carlo ray tracing simulation of view factors for diffuse solar radiation determination in cylindrical photobioreactor arrays for microalgae cultivation - Yihan Zheng; Lifeng Li; Shengkai Dai; Donghang Liu; Hao Zheng; Song Yang; Yanming Guo; Muhammad Rafique; Bo Wang; Chi-Hwa Wang; Yong Shuai (Bioresource Technology, 2025)

Co-occurrence of phytoestrogens, pyrrolizidine alkaloids and other plant secondary metabolites in rations of dairy cattle in Punjab, Pakistan - Mubarik Mahmood; Michael Sulyok; Muhammad Zafar Ullah Khan; Kanwal Rafique; Muhammad Kashif Yar; Abdur Rahman; Johannes Faas; Juan Ignacio Artavia; Rudolf Krska; Felipe Penagos-Tabares (Food Additives & Contaminants Part B-Surveillance, 2025)

Evaluation of testicular protective effects of Prunus amygdalus and zinc against cadmium induced toxicity in rats - Ayesha Tehreem Shahbaz; Faiza Zubair; Naila Riaz; Hira Kanwal; Tooba Tahir; Muhammad Talha Ishaq; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Environmental Science and Pollution Research, 2025)

Evaluation of altered biochemical and physiological responses and expression of defense-related genes in wheat following the application of plant growth regulators under drought stress - Husnain Jawad; Muhammad Bilawal Junaid; Habib Ali; Saba Saba; Shehnaz Kousar; Muhammad Saqib; Aniqa Mubeen; Ghulam Abbas; Rafique Ahmed; Amal Mohamed AlGarawi; Ashraf Atef Hatamleh; Sadam Hussain (South African Journal of Botany, 2025)

Enhancing seismic activity classification in augmented soil gas radon time series data through computational intelligence techniques - Nadeem Bashir; Adil Aslam Mir; Muhammad Osama; Saba Maqsood Abbasi; Dimitrios Nikolopoulos; Shahzad Ahmad Qureshi; Muhammad Rafique (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Effect of Aloe Vera-Based Coating on Physicochemical and Phytochemical Properties of Wild Apricot Variety - Nazish Ashraf; Imran Hayat; Nagina Rafique; Khawaja Shafique Ahmad; Muhammad Zubair Khan; Khalid J. Alzahrani; Khalaf F. Alsharif (Applied Fruit Science, 2025)

Radon measurements in soils and building materials of Kashmir - Sobia Riaz; Misbah Javed; Muhammad Rashad Khan; Muhammad Khawaja Rafique Mir; Carlo Sabbarese (Isotopes in Environmental and Health Studies, 2025)

Tuning electronic properties of NiCo2S4 nanofibers through phosphorous doping for optimized oxygen reduction and evolution reactions in Li-O2 batteries - Sana Shoukat; Yichuan Dou; Mingzhu Gao; Dongning Wan; Muhammad Shoaib; Sikandar Iqbal; Amina Tariq; Irum Rafique; Amir Said; Songze Li; Imran Haider; Jun Wang (Chemical Engineering Journal, 2025)

Boron-doped silica/chitosan-based elastic three-dimensional sponge scaffold for bone regeneration - Zheng Lei; Chunchun Li; Zhengchao Yuan; Xinyi Wang; Guangfang Cai; Panpan Shang; Yue Zhao; Muhammad Rafique; Mohamed EL-Newehy; Meera Moydeen Adulhameed; Muhammad Shafiq; Liang Song; et al. (Carbohydrate Polymers, 2025)

Plant Growth Promoting Rhizobacteria Regulated Nutrient Uptake in Quinoa (Chenopodium Quinoa Wild) Under Nutrient-Deficient Conditions Through Solubilizing Insoluble Minerals - Ejaz Rafique; Muhammad Zahid Mumtaz; Lingling Li; Inam Ullah; Talha Ali Chohan; Muhammad Waqar Alam; Adnan Mustafa; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Unveiling the future: Breakthroughs and innovations in MXene-based electrochemical sensors - Muhammad Khan; Xiaohui Sun; Faisal Attique; Muhammad Tahir Saleh; Naveed Ahmad; Kainat Atiq; Muhammad Shafi; Inas A. Ahmed; Imad Barsoum; Muhammad Shahbaz Rafique; Azeem Ullah; Amjad Hussain; et al. (Chemical Engineering Journal, 2025)

Microplastic contamination in commercial food and drink products and associated risk of potential human intake in Riyadh, Saudi Arabia - Munir Ahmad; Jahangir Ahmad; Muhammad Usama; Hamed Ahmed Al-Swadi; Mohammed Awad Mousa; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. F. Al-Farraj (Environmental Monitoring and Assessment, 2025)

Socio-economic benefits and policy implications of generating sustainable energy from municipal solid waste in Pakistan - Waqas Ahmad; Muhammad Hassan; Shah Fahad Bin Masud; Muhammad Saad Amjad; Fatin Samara; Zeshan; Mustafa Anwar; Muhammad Zeeshan Rafique; Tahir Nawaz (Energy and Climate Change, 2024)

Interactive effects of melatonin and salicylic acid on Brassica napus under drought condition - Noman Rafique; Noshin Ilyas; Muhammad Aqeel; Naveed Iqbal Raja; Ghulam Shabbir; Muhammad Ajaib; R. Z. Sayyed; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Plant and Soil, 2024)

Nutritional and medicinal plants as potential sources of enzyme inhibitors toward the bioactive functional foods: an updated review - Hammad Saleem; Anam Yaqub; Rabiya Rafique; Tahir Ali Chohan; Durr-e-Shahwar Malik; Muhammad Imran Tousif; Umair Khurshid; Nafees Ahemad; Ramasamy Ramasubburayan; Kannan RR Rengasamy (Critical Reviews in Food Science and Nutrition, 2024)

Modulating glucose metabolism and relieving hypoxia for enhanced Chemo/Photoimmunotherapy with photosensitizing enzymatic nanodrugs - Zhiyuan Zheng; Shan Lu; Yue Wu; Ayşe Başak Kayitmazer; Ayyaz Ahmad; Naveed Ramzan; Muhammad Shahid Rafique; Jintao Yang; Xiaolong Zhou; Yisheng Xu; Yi Si (Chemical Engineering Journal, 2024)

Outbreak of aflatoxicosis in a dairy herd induced depletion in milk yield and high abortion rate in Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Michael Sulyok; Kanwal Rafique; Muhammad Rizwan Khan; Qendrim Zebeli; Rudolf Krska; Barbara Metzler-Zebeli (Toxicon, 2024)

Developing a simple and efficient modeling solution for predicting key phenological stages of table grapes in a non-traditional viticulture zone in south Asia - Rizwan Rafique; Touqeer Ahmad; Muhammad Azam Khan; Mukhtar Ahmed; Gerrit Hoogenboom (International Journal of Biometeorology, 2024)

Removal of reactive dyes from textile industrial effluent using electrocoagulation in different parametric conditions of aluminum electrodes - Abdul Mannan Zafar; Asma Naeem; Muhammad Athar Minhas; Muhammad Jamal Hasan; Sania Rafique; Amir Ikhlaq (Total Environment Advances, 2024)

Silica-embedded nutrient-doped biochar improves nutrient availability and safflower (Carthamus tinctorius L.) growth in cadmium- and lead-contaminated soil - Munir Ahmad; Hamed Ahmed Al-Swadi; Jahangir Ahmad; Muhammad Usama; Mohammed Awad Mousa; Nahrir M. A. Lubis; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. Al-Farraj (Journal of Soils and Sediments, 2024)

Facile green synthesis of Phyllanthus emblica extract based Ag-NPs for antimicrobial and response surface methodology based catalytic reduction applications - Urooj Fatima; Hummera Rafique; Sadia Akram; Season Si Chen; Khalida Naseem; Jawayria Najeeb; Muhammad Tayyab (Journal of Cleaner Production, 2024)

Radon concentration in spring water as an indicator of seismic activity: a case study of the Muzaffarabad Fault in Pakistan - Sayed Qamar Abbas; Jahanzeb Khan; Muhammad Tayyib Riaz; Muhammad Rafique; Ali Zaman; Sajjad Khan (Environmental Monitoring and Assessment, 2024)

Antioxidant, anti-inflammatory, and anti-apoptotic effects of genkwanin against aflatoxin B1-induced testicular toxicity - Muhammad Umar Ijaz; Ayesha Ishtiaq; Arfa Tahir; Mughees Aizaz Alvi; Azhar Rafique; Peng Wang; Guo-ping Zhu (Toxicology and Applied Pharmacology, 2023)

Corrigendum to “Automated anomalous behaviour detection in soil radon gas prior to earthquakes using computational intelligence techniques” [J. Environ. Radioact. 203 (2019) 48-54] - Aleem Dad Khan Tareen; Asim Khawaja; Kimberlee Jane Kearfott; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Talat Iqbal; Saeed Ur Rahman (Journal of Environmental Radioactivity, 2023)

Impact of different proportions of sweet potato (Ipomoea batatas L.) flour on physical, chemical and sensory parameters of straight grade flour-based cake rusk - Hafiza Saher Rafique; Ashiq Hussain; Muhammad Nadeem; Abdul Rehman; Tahira Siddique; Ayesha Najam; Haseeb Haroon; Muhammad Rehan Arif; Shazia Yaqub; Haya Fatima; Salah Laaraj (Food and Humanity, 2023)

Pb diffusion in perfect and defective zircon for thermo/petro-chronological investigations: An atomistic approach - Matee Ullah; Urs Klötzli; Bilal Wadood; Muhammad Khubab; Fakhrul Islam; Kamran Shehzad; Rafique Ahmad (Chemical Geology, 2023)

A complete decade of multidimensional poverty in agro-environmental regions of Pakistan: a spatial evidence of agrarian and non-agrarian communities - Aneela Qadir; Muhammad Arshad; Muhammad Rafique; Aadil Hameed Shah (Environment, Development and Sustainability, 2023)

Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Muhammad Ikram; Tahira Shujah; Anum Shahzadi; Ali Haider; Aqsa Rafique; Anwar Ul-Hamid; Walid Nabgan; Syed Karrar Haider; Thamraa Alshahrani; Mohammed M. Algaradah; S. Amber Yousaf; Junaid Haider (Chemosphere, 2023)

Co-occurrence of mycotoxins and other fungal metabolites in total mixed rations of cows from dairy farms in Punjab, Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Muhammad Zafar Ullah Khan; Hafiz Muhammad Amjad Talha; Muhammad Sajid; Kanwal Rafique; Saima Naveed; Johannes Faas; Juan Ignacio Artavia; Michael Sulyok; Anneliese Müller; Rudolf Krska; et al. (Mycotoxin Research, 2023)
After India and the USA, Pakistan is the third country leading in global dairy production, a sector of very high socioeconomic relevance in Asia. Mycotoxins can affect animal health, reproduction and productivity. This study analysed a broad range of co-occurring mycotoxins and fungal secondary metabolites derived from Alternaria , Aspergillus , Fusarium , Penicillium and other fungal species. To complete this, a validated multi-metabolite liquid chromatography/electrospray ionization-tandem mass spectrometric (LC/ESI–MS/MS) method was employed, detecting 96 of > 500 tested secondary fungal metabolites. This first preliminary study demonstrated that total mixed rations (TMRs) ( n = 30) from big commercial dairy cattle farms (> 200 lactating cows) in Punjab, Pakistan, presented ubiquitous contamination with mixtures of mycotoxins. The mean of mycotoxins per sample was 14, ranging from 11 to 20 mycotoxins among all TMR samples. Metabolites derived from other fungi and Fusarium spp. showed the highest levels, frequency and diversity among the detected fungal compounds. Among the most prevalent mycotoxins were Fusarium toxins like fumonisins B1 (FB1) (93%), B2 (FB2) (100%) and B3 (FB3) (77%) and others. Aflatoxin B1 (AFB1) was evidenced in 40% of the samples, and 7% exceeded the EU maximum limit for feeding dairy cattle (5 µg/kg at 88% dry matter). No other mycotoxin exceeds the EU guidance values (GVs). Additionally, we found that dietary ingredients like corn grain, soybean meal and canola meal were related to increased contamination of some mycotoxins (like FB1, FB2 and FB3) in TMR from the province of Punjab, Pakistan. Among typical forage sources, the content of maize silage was ubiquitous. Individually, the detected mycotoxins represented relatively low levels. However, under a realistic scenario, long-term exposure to multiple mycotoxins and other fungal secondary metabolites can exert unpredictable effects on animal health, reproduction and productivity. Except for ergot alkaloids (73%), all the groups of metabolites (i.e. derived from Alternaria spp., Aspergillus spp., Fusarium spp., Penicillium spp. and other fungi) occurred in 100% of the TMR samples. At individual levels, no other mycotoxins than AFB1 represented a considerable risk; however, the high levels of co-occurrence with several mycotoxins/metabolites suggest that long-term exposure should be considered because of their potential toxicological interactions (additive or synergistic effects).

Heat-Induced Transcriptome and Genome-Wide Analysis of NHL Genes in Maize (Zea mays L.) Suggest a Role of ZmNHLs Under Heat Stress - Muhammad Shahbaz; Farrukh Azeem; Muhammad Umar Rafique; Hafiz Muhammad Shahzaib Siraj; Muhammad Rizwan (Journal of Plant Growth Regulation, 2023)

Temperature variability during the growing season affects the quality attributes of table grapes in Pothwar—insight from a new emerging viticulture region in South Asia - Rizwan Rafique; Touqeer Ahmad; Muhammad Azam Khan; Mukhtar Ahmed (International Journal of Biometeorology, 2023)

Ab initio insight into the physical properties of MgXH3 (X = Co, Cu, Ni) lead-free perovskite for hydrogen storage application - Zia ur Rehman; Muhammad Awais Rehman; Bushra Rehman; Surajudeen Sikiru; Saima Qureshi; Esraa Mousa Ali; Muhammad Awais; Mahnoor Amjad; Iqra Iqbal; Anam Rafique; Saira Bibi (Environmental Science and Pollution Research, 2023)

Nexuses between carbon emissions, trade openness, transport services, globalization index, and growth in China: targeting the sustainable development goals - Li Huang; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Abdul Haseeb; Muhammad Bashir Khan; Amir Rafique (Environmental Science and Pollution Research, 2023)

Scavenging microplastics and heavy metals from water using jujube waste-derived biochar in fixed-bed column trials - Munir Ahmad; Nahrir M.A. Lubis; Muhammad Usama; Jahangir Ahmad; Mohammad I. Al-Wabel; Hamed A. Al-Swadi; Muhammad Imran Rafique; Abdullah S.F. Al-Farraj (Environmental Pollution, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Toxicity assessment of heavy metal (Pb) and its bioremediation by potential bacterial isolates - Usaal Tahir; Mariam Zameer; Qurban Ali; Ayesha Rafique; Syeda Maham Ali; Muhammad Umer Arif; Imtiaz Nawaz; Saif ul Malook; Daoud Ali (Environmental Monitoring and Assessment, 2023)

Late-mover advantages, innovation capability, and leapfrogging upgrading of low-carbon technology: evidence from Chinese enterprise groups - Shi Deqiang; Chen Zhijun; Muhammad Zahid Rafique (Environmental Science and Pollution Research, 2023)

Singular spectral and control chart analysis of soil radon and thoron time series for forecasting seismic activities - Awais Rasheed; Muhammad Osama; Dimitrios Nikolopoulos; Muhammad Rafique (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Efficient resource utilization of the electricity distribution sector using nonparametric data envelopment analysis and influential factors - Majid Ikram; Muhammad Zahid Rafique; Kamel Si Mohammed; Rida Waheed; Diogo Ferraz (Utilities Policy, 2023)

Controlling Arsenic Contamination Through Bentonite Clays: a Batch Sorption Study - Muhammad Umair; Ayaz Mehmood; Shah Rukh; Ahmad Khan; Zahoor Ahmad; Mazhar Rafique; Kouser Majeed Malik; Ali Raza Gurmani (Journal of Soil Science and Plant Nutrition, 2023)

The influence of climate change, green innovation, and aspects of green dynamic capabilities as an approach to achieving sustainable development - Muhammad Arshad; Chen Kun Yu; Aneela Qadir; Muhammad Rafique (Environmental Science and Pollution Research, 2023)

Fabrication of Nano-bentonite-Based Organo-minerals Composites of Biochar: Characterization and Application to Remove Arsenate from Contaminated Water - Jahangir Ahmad; Abdullah S. Al-Farraj; Munir Ahmad; Mohammad I. Al-Wabel; Muhammad Imran Rafique; Hamed Ahmed Al-Swadi (Water, Air, & Soil Pollution, 2023)

Seasonal variability in the effect of temperature on key phenological stages of four table grapes cultivars - Rizwan Rafique; Touqeer Ahmad; Mukhtar Ahmed; Muhammad Azam Khan; Carol J. Wilkerson; Gerrit Hoogenboom (International Journal of Biometeorology, 2023)

Urinary PAHs metabolites in Karakoram Highway’s heavy traffic vehicle (HTV) drivers: evidence of exposure and health risk - Maria Rafique; Audil Rashid; Shu Tao; Bin Wang; Aman Ullah; Lun Lu; Habib Ullah; Muhammad Ubaid Ali; Waqas Naseem (Environmental Geochemistry and Health, 2023)

Impact of rock-water interaction on hydrogeochemical characteristics of groundwater: Using multivariate statistical, water quality index and irrigation indices of chachro sub-district, thar desert, sindh, Pakistan - Muhammad Soomar Samtio; Asghar Ali alias Daahar Hakro; Taj Muhammad Jahangir; Abdul Shakoor Mastoi; Muhammad Farooque Lanjwani; Riaz Hussain Rajper; Rafique Ahmed Lashari; Muhammad Hassan Agheem; Muhammad Waseem Noonari (Groundwater for Sustainable Development, 2023)

Genetically engineered microorganisms for environmental remediation - Hamza Rafeeq; Nadia Afsheen; Sadia Rafique; Arooj Arshad; Maham Intisar; Asim Hussain; Muhammad Bilal; Hafiz M.N. Iqbal (Chemosphere, 2023)

Silica modified biochar mitigates the adverse effects of salt and drought stress and improves safflower (Carthamus tinctorius L.) growth - Munir Ahmad; Muhammad I. Rafique; Mutair A. Akanji; Mohammad I. Al-Wabel; Hamed A. Al-Swadi; Abdullah S. F. Al-Farraj (Journal of Soils and Sediments, 2023)

Biochemical Characterization and Potential of Bacillus safensis Strain SCAL1 to Mitigate Heat Stress in Solanum lycopersicum L. - Tehmeena Mukhtar; Fawad Ali; Mazhar Rafique; Javed Ali; Muhammad Siddique Afridi; Donald Smith; Shehzad Mehmood; Amna; Alfred Souleimanov; Ghulam Jellani; Tariq Sultan; Farooq Hussain Munis; et al. (Journal of Plant Growth Regulation, 2023)

Neurotoxic effects of environmental contaminants—measurements, mechanistic insight, and environmental relevance - Nadia Afsheen; Sadia Rafique; Hamza Rafeeq; Kanwal Irshad; Asim Hussain; Zille Huma; Vineet Kumar; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Fabrication of polysulfone mixed matrix membrane for wastewater treatment - Kousar Parveen; Uzaira Rafique; Muhammad Javed Akhtar (Journal of Environmental Health Science and Engineering, 2022)

Validation of in vitro grafting using indigenous wild grapevines as rootstock with commercial scion varieties - Fahad Nazir; Touqeer Ahmad; Muhammad Ajmal Bashir; Rizwan Rafique; Irfan Ali; Cristian Silvestri; Eddo Rugini; Sadar Uddin Siddiqui (Acta Physiologiae Plantarum, 2022)

Heavy metal remediation and resistance mechanism of Aeromonas , Bacillus , and Pseudomonas : A review - Ali Fakhar; Bushra Gul; Ali Raza Gurmani; Shah Masaud Khan; Shafaqat Ali; Tariq Sultan; Hassan Javed Chaudhary; Mazhar Rafique; Muhammad Rizwan (Critical Reviews in Environmental Science and Technology, 2022)

Clean and sustainable transportation through electric vehicles — a user survey of three-wheeler vehicles in Pakistan - Mohammad Aamir Khan; Syed Fawad Bokhari; Aazir Khan; Muhammad Saad Amjad; Arooj Mobasher Butt; Muhammad Zeeshan Rafique (Environmental Science and Pollution Research, 2022)

Viruses as tools in gene therapy, vaccine development, and cancer treatment - Musab bin Umair; Fujimura Nao Akusa; Hadia Kashif; Seerat-e-Fatima; Fatima Butt; Marium Azhar; Iqra Munir; Muhammad Ahmed; Wajeeha Khalil; Hafiz Sharyar; Shazia Rafique; Muhammad Shahid; et al. (Archives of Virology, 2022)

Does economic complexity matter for environmental sustainability? Using ecological footprint as an indicator - Muhammad Zahid Rafique; Abdul Majeed Nadeem; Wanjun Xia; Majid Ikram; Hafiz Muhammad Shoaib; Umer Shahzad (Environment, Development and Sustainability, 2022)

Measurement of age-dependent radiation ingestion doses due to gross alpha and gross beta exposure from medicinal plants - Muhammad Rafique; Chand Shahzadi; Abdul Jabbar; Mumtaz Khan; Saeed Ur Rahman; Syed Shujahat Hussain Bukhari; Shahab Ahmed Abbasi; Nasar Ahmed (Isotopes in Environmental and Health Studies, 2022)

A review on sources of heavy metals, their toxicity and removal technique using physico-chemical processes from wastewater - Muhammad Rafique; Syeda Hajra; Muhammad Bilal Tahir; Syed Sajid Ali Gillani; Muneeb Irshad (Environmental Science and Pollution Research, 2022)

The effect of fiscal decentralization, environmental regulation, and economic development on haze pollution: empirical evidence for 270 Chinese cities during 2007–2016 - Li Xiao-Sheng; Lu Yu-Ling; Muhammad Zahid Rafique; Mahdi Ghaemi Asl (Environmental Science and Pollution Research, 2022)

Estimation of a trend of meteorological and hydrological drought over Qinhuai River Basin - Mohammad Ilyas Abro; Ehsan Elahi; Ram Chand; Dehua Zhu; Jan Muhammad; Muhammad Rafique Daudpoto; Abdul Majid Soomro; Murad Ali Khaskheli (Theoretical and Applied Climatology, 2022)

Re-investigating the nexuses of renewable energy, natural resources and transport services: a roadmap towards sustainable development - Syed Abdul Rehman Khan; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Amir Rafique; Mustansar Hayat; Saqib Gulzar; Zhang Yu (Environmental Science and Pollution Research, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Impact of water–sediment interaction on hydrogeochemical signature of dug well aquifer by using geospatial and multivariate statistical techniques of Islamkot sub-district, Tharparkar district, Sindh, Pakistan - Muhammad Soomar Samtio; Khadim Hussain Rajper; Asghar Ali alias Daahar Hakro; Muhammad Farooque Lanjwani; Abdul Qayoom Mughari; Rakhshanda Sadaf; Riaz Hussain Rajper; Abdul Shakoor Mastoi; Muhammad Hassan Agheem; Rafique Ahmed Lashari; Taj Muhmmad Jahangir (Arabian Journal of Geosciences, 2022)

Mechanisms of microbes to combat salinity in soil by producing secondary metabolites - Moniba Zahid Mahmood; Sumera Bibi; Muhammad Shahzad; Ali Fakhar; Mazhar Rafique; Abdul Qayyum (Arabian Journal of Geosciences, 2022)

Next-generation sequencing studies on the E1-HVR1 region of hepatitis C virus (HCV) from non-high-risk HCV patients living in Punjab and Khyber Pakhtunkhwa, Pakistan - Javeria Rafique Rao; Shazia Rafique; Amjad Ali; Gouhar Rehman; Muhammad Ilyas; Muhammad Idrees (Archives of Virology, 2021)

Sonolytic-ozonation technology for sanitizing microbial contaminants and pesticide residues from spinach (Spinacia oleracea L.) leaves, at household level - Zarghona Siddique; Aman Ullah Malik; Muhammad Rafique Asi; Raheel Anwar; Muhammad Inam Ur Raheem (Environmental Science and Pollution Research, 2021)

Determination of pesticide residues in dates using UHPLC-QqQ-MS/MS: method development and validation - Somia Qayyum; Touqeer Taj; Muhammad Tauseef; Muhammad Ishtiaq; Nazia Rafique; Karam Ahad; Muhammad Aslam Mirza; Muhammad Aziz Choudhary; Farrakh Mehboob (Environmental Monitoring and Assessment, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Event-based and continous flood modeling in Zijinguan watershed, Northern China - Rajeev Katwal; Jianzhu Li; Ting Zhang; Chunqi Hu; Muhammad Akbar Rafique; Yanchen Zheng (Natural Hazards, 2021)

Correction to: Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

Anomaly Classification for Earthquake Prediction in Radon Time Series Data Using Stacking and Automatic Anomaly Indication Function - Adil Aslam Mir; Fatih Vehbi Çelebi; Muhammad Rafique; M. R. I. Faruque; Mayeen Uddin Khandaker; Kimberlee Jane Kearfott; Pervaiz Ahmad (Pure and Applied Geophysics, 2021)

Rising Metals Concentration in the Environment: A Response to Effluents of Leather Industries in Sialkot - Noreen Khalid; Zarrin Fatima Rizvi; Nousheen Yousaf; Shujaul Mulk Khan; Ali Noman; Muhammad Aqeel; Komal Latif; Asmara Rafique (Bulletin of Environmental Contamination and Toxicology, 2021)

Comparative efficacy of mitigation techniques for the detoxification of Prunus persica (L.) from selected pesticide residues - Neelab; Muhammad Rafique Asi; Sundas Kali; Muhammad Asam Riaz; Amir Waseem; Muhammad Mazhar Iqbal; Nauman Ahmad; Mazhar Iqbal; Noshin Masood; Mazhar Iqbal Zafar (Environmental Science and Pollution Research, 2020)

Spatial distribution of microplastics in soil with context to human activities: a case study from the urban center - Anam Rafique; Muhammad Irfan; Mehvish Mumtaz; Abdul Qadir (Environmental Monitoring and Assessment, 2020)

Synthesis of nickel nanoparticles using Citrullus colocynthis stem extract for remediation of Reactive Yellow 160 dye - Shumaila Kiran; Muhammad Asim Rafique; Sarosh Iqbal; Sofia Nosheen; Saba Naz; Abdur Rasheed (Environmental Science and Pollution Research, 2020)

The effects of FDI, technological innovation, and financial development on CO2 emissions: evidence from the BRICS countries - Muhammad Zahid Rafique; Yafei Li; Abdul Razaque Larik; Malepekola Precious Monaheng (Environmental Science and Pollution Research, 2020)

Extracting mass concentration time series features for classification of indoor and outdoor atmospheric particulates - Lal Hussain; Wajid Aziz; Sharjil Saeed; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Seong-O Shim; Sania Aftar; Jawad-ur-Rehman Pirzada (Acta Geophysica, 2020)

Type 1 Fimbriae and Motility Play a Pivotal Role During Interactions of Salmonella typhimurium with Acanthamoeba castellanii (T4 Genotype) - Talha Mannan; Muhammad Wasim Rafique; Muhammad Haroon Bhatti; Abdul Matin; Irfan Ahmad (Current Microbiology, 2020)

Impact of financial development on CO2 emissions: A comparative analysis of developing countries (D8) and developed countries (G8) - Hafiz Muhammad Shoaib; Muhammad Zahid Rafique; Abdul Majeed Nadeem; Shaoan Huang (Environmental Science and Pollution Research, 2020)

In situ immobilization of Cr and its availability to maize plants in tannery waste–contaminated soil: effects of biochar feedstock and pyrolysis temperature - Muhammad Imran Rafique; Adel R. A. Usman; Munir Ahmad; Abdelazeem Sallam; Mohammad I. Al-Wabel (Journal of Soils and Sediments, 2020)

First report of molecular characterization of Aspergillus flavus from maize in Pakistan - Najeeb Ullah; Khalid Pervaiz Akhtar; Syed Wajih ul Hassan; Muhammad Rafique Asi; Yumna Sadef (Journal of Plant Pathology, 2019)

Effects of Rhizophagus clarus and biochar on growth, photosynthesis, nutrients, and cadmium (Cd) concentration of maize (Zea mays) grown in Cd-spiked soil - Mazhar Rafique; Ibrahim Ortas; Muhammad Rizwan; Tariq Sultan; Hassan Javed Chaudhary; Mehmet Işik; Oğuzhan Aydin (Environmental Science and Pollution Research, 2019)

Achieving an environmentally sustainable outcome for the Gulpur hydropower project in the Poonch River Mahaseer National Park, Pakistan - Cate Brown; Vaqar Zakaria; Alison Joubert; Muhammad Rafique; Jahanzeb Murad; Jackie King; Jessica Hughes; Pablo Cardinale; Leeanne Alonzo (Sustainable Water Resources Management, 2019)

Removal of pirimicarb from agricultural waste water using cellulose acetate–modified ionic liquid membrane - Sana Zulfiqar; Uzaira Rafique; Muhammad Javed Akhtar (Environmental Science and Pollution Research, 2019)

Engineered biochar composites with zeolite, silica, and nano-zerovalent iron for the efficient scavenging of chlortetracycline from aqueous solutions - Munir Ahmad; Adel R. A. Usman; Muhammad Imran Rafique; Mohammad I. Al-Wabel (Environmental Science and Pollution Research, 2019)

Tattooing trend: major cause of HCV transmission among youngsters - Braira Wahid; Komal Saleem; Nouman Rasool; Shazia Rafique; Amjad Ali; Muhammad Waqar; Muhammad Idrees (Infectious Diseases, 2018)

Classification of rocks radionuclide data using machine learning techniques - Abdul Razzaq Khan; Adil Aslam Mir; Sharjil Saeed; Muhammad Rafique; Khawaja M. Asim; Talat Iqbal; Abdul Jabbar; Saeed Ur Rahman (Acta Geophysica, 2018)

Ellis–van Creveld syndrome and profound deafness resulted by sequence variants in the EVC / EVC2 and TMC1 genes - Muhammad Umair; Heide Seidel; Ishtiaq Ahmed; Asmat Ullah; Tobias B. Haack; Bader Alhaddad; Abid Jan; Afzal Rafique; Tim M. Strom; Farooq Ahmad; Thomas Meitinger; Wasim Ahmad (Journal of Genetics, 2017)

HCV-induced regulatory alterations of IL-1β, IL-6, TNF-α, and IFN-ϒ operative, leading liver en-route to non-alcoholic steatohepatitis - Rabia Nawaz; Sadia Zahid; Muhammad Idrees; Shazia Rafique; Muhammad Shahid; Ammara Ahad; Iram Amin; Iqra Almas; Samia Afzal (Inflammation Research, 2017)

Differential effects of cadmium and chromium on growth, photosynthetic activity, and metal uptake of Linum usitatissimum in association with Glomus intraradices - Amna; Naeem Ali; Sajid Masood; Tehmeena Mukhtar; Muhammad Aqeel Kamran; Mazhar Rafique; M. Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2015)

Removal of Cd, Cr, and Pb from aqueous solution by unmodified and modified agricultural wastes - Muhammad Mahmood-ul-Hassan; Vishandas Suthor; Ejaz Rafique; Muhammad Yasin (Environmental Monitoring and Assessment, 2015)

Morpho-anatomical and physiological attributes for salt tolerance in sewan grass (Lasiurus scindicus Henr.) from Cholistan Desert, Pakistan - Nargis Naz; Tanzila Rafique; Mansoor Hameed; Muhammad Ashraf; Riffat Batool; Sana Fatima (Acta Physiologiae Plantarum, 2014)

Studies on the role of neutralizing antibodies against envelope genes in resolving HCV pseudo-particles infection - Shazia Rafique; Muhammad Idrees; Amjad Ali; Muhammad Iqbal (Molecular Biology Reports, 2014)

Generation of infectious HCV pseudo typed particles and its utilization for studying the role of CD81 & SRBI receptors in HCV infection - Shazia Rafique; Muhammad Idrees; Amjad Ali; Kashif Iqbal Sahibzada; Muhammad Iqbal (Molecular Biology Reports, 2014)

Aflatoxin M 1 in milk from urban and rural farmhouses of Punjab, Pakistan - Shahzad Zafar Iqbal; Muhammad Rafique Asi; Jinap Selamat (Food Additives & Contaminants Part B-Surveillance, 2014)

NutriTRAILomics in prostate cancer: time to have two strings to one’s bow - Ammad Ahmad Farooqi; Aamir Rana; Asma M. Riaz; Ammara Khan; Muhammad Ali; Sara Javed; Shahzeray Mukhtar; Sehrish Minhaj; Javeria Rafique Rao; Javairia Rajpoot; Rafia Amber; Fiza Asif Javed; et al. (Molecular Biology Reports, 2012)